Anonymous green heroes in the making - Arcuri, María Emilia (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
The Anonymous Heroes Project describes an intercultural citizenship project for the language classroom, based on environmental education. It aims to raise children’s awareness on waste treatment and reflect on people’s attitudes towards the environment. It is intended for teachers who support education for democratic citizenship and want to provide children with the set of skills needed to critique, evaluate, accept responsibility on common issues and take action.